PERANCANGAN SISTEM KONSTRUKSI MEKANIK 3D PRINTER GEOPOLYMER TYPE CARTESIAN - Setiawan, Heri; Nopriyanti, Rani; Adi Soetopo, Antonius; Rusmana, Nandang; Gunawan, Iwan; Pandoe; Budi Harja, Herman; Rahmat Hadi, Faisal (Jurnal Rekayasa Mesin, 2024)
The population growth in Indonesia continues to increase every year, which causes a higher level of demand for civil buildings and houses. 3D concrete printing is an innovative construction method that has recently begun to be applied to the construction industry and has proven to be profitable in terms of optimizing construction time, cost, design flexibility and error reduction as well as being environmentally friendly. The geopolymer 3D printer is a 3D concrete printing machine specifically for extruding geopolymer mortar materials. This study aims to design a mechanical construction system for a 3D printer geopolymer machine. Geopolymer mortar has a unique strength compared to cement mortar and dries faster so it has better molding properties. The design of the cartesian type geopolymer 3D printer machine uses the VDI 2222 design method which consists of planning, conceptualizing, designing, and finishing. Based on this design method, a printing area of 5m x 5m x 3m is designed with a maximum printing speed of 100 mm/s. The results of this design meet the demands and are stated to be technically good in static calculations.